The Theory of Plane Area at the Crossroads Philosophical, Historical, and Logical Perspectives - Giovannini, Eduardo N.; Haeusler, Edward Hermann; Lassalle Casanave, Abel (Logic, Epistemology, and the Unity of Science, 2024)
XXII, 142 p. 78 illus., 5 illus. in color.